Berlitz French CD pack. - Berlitz Publishing Company (Singapore Berlitz Pub., 2002)
Berlitz Phrasebook and Dictionary French: a convenient, contemporary travel companion from Berlitz's trusted language experts ·
Basic expressions -- Accommodations -- Eating out -- Travel -- Sightseeing -- Leisure -- Making friends -- Stores & services -- Health -- Numbers -- Days -- Greetings -- Time.
Accompanying phrase book entitled: French phrase book.
90201
Keywords: French language -- English; French language -- Self-instruction.; French language -- Study and teaching -- English speakers -- Audio-visual aids; French language